Sodium MRI of T1 high signal intensity in the dentate nucleus due to gadolinium deposition in multiple sclerosis - Eisele, Philipp; Szabo, Kristina; Meyer, Melissa; Zöllner, Frank G.; Schad, Lothar R.; Schönberg, Stefan; Gass, Achim (Journal of neuroimaging, 2017)
Background and purpose: Recently, several studies reported increased signal intensity (SI) of the dentate nucleus (DN) on unenhanced T1-weighted magnetic resonance imaging (MRI) as a possible consequence of multiple applications of gadolinium-based contrast agents. The aim of this study was to investigate with sodium (23Na) MRI possible tissue abnormalities of the DN in multiple sclerosis (MS) patients. Methods: Sodium and conventional MRI were performed on a clinical 3T scanner. Total sodium concentrations (TSCs) of the DN, as well as DN-to-pons and DN-to-cerebellum SI ratios on unenhanced T1-weighted MRI were calculated. Results: A total of 18 subjects (6/18 normal controls, 12/18 MS patients [6/12 with T1 hyperintense DN]) were investigated. There was no significant difference of TSC values of the DN in MS patients with a T1-hyperintense DN (33.70 ± 2.14 mM) compared to MS patients without those signal abnormalities (33.29 ± 1.67 mM; P = .67) or to healthy controls (33.14 ± 1.12; P = .32). Conclusions: Normal sodium signal in the T1-hyperintense DN in MS patients may point to relative tissue integrity despite gadolinium deposition in this area.